1)Բացե՛ք փակագծերն ու բերե՛ք կատարյալ տեսքի.
ա) (x + 3)(x + 6) =x² + 6x + 3x + 18 = x² + 9x + 18
բ) (3a + 4)(2a − 7) = 6a² – 21a + 8a – 28 = 6a² – 28 – 13a
գ) (9x2 − 4x)(9x + 4)= 9x³ + 36x² – 36x² – 16x = 9x³ – 16x
դ) (2y2 − b2)(3y2 + 4b2) = 6y⁴ + 8b²y² – 3y²b² – 4b⁴ = 6y⁴ + 5b²y² – 4b⁴
ե) (a − b)(a + b) = a² – b²
զ) (7a − 3)(7b + 3) = 49ab + 21a – 21b – 9
2)Բացե՛ք փակագծերն ու միավորե՛ք նման միանդամները.
ա) (ax + 5)(bx − 1) = abx² – ax + 5bx – 5
բ) (7b2 + 3a3)(3a3 − 7b2) = 21a³b² – 49b⁴ + 9a⁶ – 21a³b² = -49b⁴ + 9a⁶
գ) (y − 2)(y + 1) = y² + y – 2y – 2= y² – y – 2
դ) (−x + 5)(x − 1) = -x² + x + 5x – 5 = -x² + 6x – 5
3)Բերե՛ք կատարյալ տեսքի.
ա) 5(2 − 3c) + 7(3c + 1) = 10 – 15c + 21c + 7 = 17 + 6c
բ) 6x(x − 2) − 3(2x2 − 4) = 6x² – 12x – 6x² + 12 = -12x + 12
գ) (a + b)( a2 − ab + b2) = a³ – a²b + ab² + a²b – ab² + b³ = a³ + b³
դ) (x + 1)(y + 1) + (x − 1)(y − 1) = xy + x + y + 1 + xy – x – y + 1 = 2xy + 2